(untitled) (La Aljaba, Segunda Época. Revista de Estudios de la Mujer, 2017)
Elsa Drucaroff is Professor of Arts and Doctor of Social Sciences, literary critic and author of several novels as La patria de las mujeres and El infierno prometido.. As a result of her conference in the XII Jornadas de Historia de las Mujeres y VII Congreso Iberoamericano de Género (UNCo, 2015), we asked Drucaroff about the articulation between literature and gender. We reviewed, in the first place, the writing styles and reading operations carried out by the literary criticism. Second, we became interested in the challenges she faces because of her double position as a writer and as a critic specialized in gender theories. We also considered the variants and constants of the women’s representation in argentinean literary tradition and in the new generations writers. Finally, we inquired about the recent publication of novels that show an alternative view of our history. The topics of women’s place in society and the meaning of homeland turn into a discussion that develops a theoretical incursion on the intersections between class and gender which she studies in her next book, Otro Logos. Signos, política, discursos.